A phase II trial of bendamustine in combination with ofatumumab in patients with relapsed or refractory marginal zone B‐cell lymphomas. Issue 1 (6th November 2020) - Vannata, Barbara; Vanazzi, Anna; Negri, Mara; Liptrott, Sarah Jayne; Bartosek, Anna Amalia; Miani, Monica; Di Sanzo, Alessandro; Cavalli, Franco; Zucca, Emanuele; Stathis, Anastasios
Abstract: Marginal zone lymphomas (MZLs) are indolent yet incurable lymphomas with frequent relapses following therapy. For patients with relapsed/refractory disease, no standard therapies exist. Here we report results of an exploratory phase II study aimed at assessing the efficacy and safety of the alkylator agent bendamustine in combination with the second‐generation anti‐CD20 monoclonal antibody, ofatumumab, in patients with relapsed or refractory MZL. Patients with MZL and previously treated with at least one line of systemic therapy were eligible. Treatment consisted in bendamustine (90 mg/m 2 on days 1 and 2) and ofatumumab (1000 mg on day 1) in 28‐day cycles for up to six cycles. Sixteen patients were included in the trial. In one patient, the diagnosis was revised after two cycles of treatment and was excluded from the efficacy analysis. Among 15 patients with MZL, 14 were evaluable for response: the overall and complete response rates were 92.9% and 57.1%, respectively. The median duration of response was 30.4 months (95% confidence interval [CI], 15.5 –not estimable) and 2‐years progression‐free survival 77% (95% CI, 43%–92%). Fifteen patients (94%) experienced grade 3–4 adverse events. Toxicity was mostly hematological. Neutropenia grade ≥3 was recorded in 27% of patients, lymphocytopenia in 93%, and infections and febrile neutropenia each in 13%. One patient discontinued treatment due to myocardial infarction; no treatment‐related deaths occurred. The combination of bendamustine with ofatumumab was active with an acceptable toxicity profile in this small phase II trial and can be considered for further investigation in relapsed/refractory MZL patients.